Preferences of modern mobile app users - Kamil Kasztelan; Jakub Smołka (Journal of Computer Sciences Institute, 2022)
Each user group has its own preferences for mobile applications. A better app will increase the satisfaction of existing users and encourage new people to download it. People are used to it that it's hard to get rid of them. A survey was conducted in the Włodawa district in the first quarter of 2020, in which 150 random people took part. It has been noticed that life with a mobile device in hand has become a habit. Users more willingly and more often use the help of mobile devices during shopping while looking for product information and promotions. It has been observed that users pay more attention to application security, wanting to be sure that their data is safe. A small group of people would give up their mobile device and start using traditional methods